(untitled) (Economic studies journal, 2021)
Abstract The study aimed to identify the challenges (academic and scientific "cognitive") that face the faculties of economics students in Libyan universities when preparing graduation research from the viewpoint of faculty members at the Faculty of Economics, Al-Marqab University And to suggest a set of mechanisms to address these challenges, The study relied on descriptive and analytical approaches, The researchers used the questionnaire list method to collect data from all faculty members at the Faculty of Economics and Trade, Al- Marqab University,The study found that students of the Faculty of Economics and Trade face a set of challenges when preparing graduation research, namely: First, academic challenges, the most important of which are (The lack of incentive incentives for distinguished research, The university’s lack of interest in providing modern information to students by subscribing to the websites of international scientific journals, The low level of services provided by the college library),Second, "cognitive" scientific challenges are among the most important (The poor ability of students to use appropriate statistical methods, And their weak language ability to express and formulate sentences, And the lack of their experience in gathering information and the lack of experience of students in preparing the research plan),One of the most important mechanisms to face these challenges (Preparing seminars and workshops on how to prepare graduation research and the uses of statistical methods in graduation research, The college administration should assist students in obtaining the information necessary for graduation research by addressing the relevant authorities and urging them to cooperate with the student and give him all the data and information that he needs, Providing a good office service for students by providing modern references periodically and establishing the electronic library at the university and college level, And to review the teaching burden of the faculty members in a manner that provides them with sufficient time to supervise the graduation research),One of the most important recommendations of the study is to work on forming a partnership with the economic units in society to identify their problems, And directing graduation students to study these problems in order to enhance accessibility of information with ease, And work to establish competitions for the best graduation project in order to develop the spirit of competition among students.